An ADCP study of subtidal scale density-driven exchange in Saldanha Bay, South Africa - Stewart, Helen Frances (University of Cape Town, 2014)
Bibliography: leaves 33-34. === An ADCP and water-column temperature study was conducted to determine the circulation aspect of subtidal-scale, density-driven exchange in Saldanha Bay, South Africa. Density-driven exchange conditions develop in response to synoptic-scale wind events in the southern Benguela region, even under light (<5m s-') wind conditions. During a density-driven exchange event, directionally opposing bi-level flow, similar to an estuarine system, develops in response to remote upwelling-favourable winds. The bi-level flow component occurs in two distinct bands, bayward at 0-9m height from bottom and seaward 15-20m height off bottom, and is very sensitive to changes in wind forcing. Observations of current behaviour are added to the four-phase conceptual model of density-driven exchange developed by Monteiro and Largier (1999). In addition, estimates of bay flushing based on ADCP current velocities and the four-phase conceptual model are calculated and implications of shelf water influx into Saldanha Bay are discussed.